Refocusing Research on Sexually Transmitted Infections - Eisinger, Robert W (J Infect Dis, 2019)
This article highlights biomedical research goals for the development of critical tools, including innovative diagnostics, safe and effective vaccines, and new and improved therapeutics, necessary to achieve an end to the global epidemic of sexually transmitted infections. The incidence of sexually transmitted infections (STIs), including gonorrhea, syphilis, chlamydia, and trichomoniasis, is increasing by over 1 million new cases daily and represents a global public health crisis. There is an alarming increase of gonorrhea and syphilis among men who have sex with men and bisexual men, 2 key populations also at high risk for human immunodeficiency virus. A refocused, dedicated, and intensive biomedical research program is needed targeting development of innovative diagnostics, safe and effective vaccines, and new and improved therapeutics. This article highlights biomedical research goals providing critical tools necessary to achieve an end to the global STIs epidemic.